2019
DOI: 10.1155/2019/4024958
|View full text |Cite
|
Sign up to set email alerts
|

Physicochemical Characterization and Biocompatibility of SPION@Plasmonic @Chitosan Core-Shell Nanocomposite Biosynthesized from Fungus Species

Abstract: In this work we aim to manipulate green route for the synthesis of core-shell maghemite-based Ag nanoparticles functionalized with chitosan. Three fungal species, Aspergillus deflectus, Fusarium oxysporum, and Penicillium pinophilum, were used in the process of synthesis to select the best among them for the production. The physicochemical parameters of produced nanoparticles and mediated cytotoxicity assessment for their potential medical application have been performed using Fourier transform infrared (FTIR)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 28 publications
2
2
0
Order By: Relevance
“…The strong stretching absorption band could identify the presence of SPIONs core at 563.18 cm −1 in the G‐SPIONs, which corresponded to the FeO bond agreed with the finding of Pham et al (2017), Karimzadeh et al (2017), Villamin and Kitamoto (2018) Khedri et al (2018), Eid et al (2019). The bands at 3417.68 and 1,620.11 cm −1 in G‐SPIONs can be assigned to the OH stretching modes and bending vibration of Fe 3 O 4 , respectively (Eid et al, 2019; Karimzadeh et al, 2017; Khedri et al, 2018; Mahdavi et al, 2013; Petcharoen & Sirivat, 2012; Pham et al, 2017; Sodipo & Azlan, 2015; Villamin & Kitamoto, 2018). In addition, the appearance of two strong bands in G‐SPIONs at 1209.30 cm −1 and 1,155.29 cm −1 were ascribed to CO bond stretching agreed with the findings of Sivakumar et al (2017) and Esfandiary et al (2017), while another one peak was appeared at 815.84 cm −1 suggested that there must be strong vibrational interaction between SPIONs and glucose (Sivakumar et al, 2017).…”
Section: Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…The strong stretching absorption band could identify the presence of SPIONs core at 563.18 cm −1 in the G‐SPIONs, which corresponded to the FeO bond agreed with the finding of Pham et al (2017), Karimzadeh et al (2017), Villamin and Kitamoto (2018) Khedri et al (2018), Eid et al (2019). The bands at 3417.68 and 1,620.11 cm −1 in G‐SPIONs can be assigned to the OH stretching modes and bending vibration of Fe 3 O 4 , respectively (Eid et al, 2019; Karimzadeh et al, 2017; Khedri et al, 2018; Mahdavi et al, 2013; Petcharoen & Sirivat, 2012; Pham et al, 2017; Sodipo & Azlan, 2015; Villamin & Kitamoto, 2018). In addition, the appearance of two strong bands in G‐SPIONs at 1209.30 cm −1 and 1,155.29 cm −1 were ascribed to CO bond stretching agreed with the findings of Sivakumar et al (2017) and Esfandiary et al (2017), while another one peak was appeared at 815.84 cm −1 suggested that there must be strong vibrational interaction between SPIONs and glucose (Sivakumar et al, 2017).…”
Section: Resultssupporting
confidence: 88%
“…The strong stretching absorption band could identify the presence of SPIONs core at 563.18 cm À1 in the G-SPIONs, which corresponded to the Fe O bond agreed with the finding of Pham et al (2017), Karimzadeh et al (2017), Villamin and Kitamoto (2018) Khedri et al (2018),Eid et al (2019). The bands at 3417.68 and 1,620.11 cm À1 in G-SPIONs can be assigned to the O H stretching modes and bending vibration of Fe 3 O 4 , respectively(Eid et al, 2019;Karimzadeh et al, 2017;Khedri et al, 2018;Mahdavi et al, 2013;Petcharoen & Sirivat, 2012;Pham et al, 2017;Sodipo & Azlan, 2015;Villamin & Kitamoto, 2018). In addition, the appearance of two strong…”
supporting
confidence: 89%
“…where α is the absorption coe cient, A is a constant, ν is the photon frequency, h is Plank's constant, and E g is the bandgap energy. The absorption coe cient (α) was calculated for each value based on the absorption data [29]. The exponent n's value is determined by the type of transition like n = 1/2 for indirect bandgap and allowed transition; n=2 for direct transition; and n=3/2 for directly forbidden transition.…”
Section: Optical Studymentioning
confidence: 99%
“…Owing to their unique and desirable superparamagnetic properties, SPIONs exhibit great potentiality as targeted drug nanoparticles for in vivo drug delivery . Magnetic nanoparticles containing an SPION core–shell and a polymer coating could also retain their targeted-delivery functionality. , For example, Greneche et al synthesized magnetic O -carboxymethylchitosan nanoparticles for carrying meleimidic compounds. The magnetic nanoparticles showed high incorporation efficiency of maleimides, sustained-release character, and increased mass release when using an external magnetic field .…”
Section: Introductionmentioning
confidence: 99%